SOLUSI RESTRUKTURALISASI KREDIT DARI DAMPAK COVID-19 PADA SUDUT PANDANG QAWAID FIQHIYAH - AHMAD AFIF (Sekolah Tinggi Agama Islam AL Aqidah Al Hasyimiyyah Jakarta, 2020)
It is interesting to study and look for innovative solutions in this research by prioritizing the response of the fiscal policy package during the pandemic period of the government with other principles and approaches, so that in addition to find proposals as innovative solutions it also includes elements of Islamic values. Why talk about credit restructuring solutions through qawaid fiqhiyah ? because of several articles and journals and theories that have used methods and approaches from conventional and social Islamic instruments, but with this method and approach the writer tries to explore all methods and approaches are indeed pure from the muiner fiqh product enginer.Therefore, the discussion will be specific to two things: first, credit restructuring solutions and the security system of Islamic financial institutions in the mitigation area in the pandemic period, second, Compatibility between business and sharia policies.Qâidah fiqhiyyah approach by drawing conclusions from empirical and historical datas, concretely the usûl method by way of; first, istimbat al-Ahk with the determination of the analysis, classification of arguments and the conditions underlying the research. Secondly, tadhbiq al-Ahkam for the application of the analysis of research subject knowledge related to the causes, conditions and causes of obstruction of the application of the qawaid fiqhiyah approach. Afterwards a framework will be drawn up with the results of the analysis.From the discussion above, we can conclude that On the restructuring pattern side there are at least five recommendations, namely: Deferring the principal of the loan; Delay of principal + interest / margin; Postponement of remaining principal; Extra time; and Decrease in interest in People's Business Credit (KUR). While in making the pattern of Islamic banking must mitigate with two things, namely: The concept of profit and loss sharing and investment risk factors. Besides, the compatibility between business and sharia policies is in accordance with some qawaid fiqhiyah about finance.